Fixed-dose trial of the single isomer SSRI Escitalopram in depressed outpatients - Burke, William J.; Gergel, Ivan; Bose, Anjana (The Journal of Clinical Psychiatry, 2002)
Escitalopram (ESC) is the single isomer responsible for the serotonin reuptake inhibition produced by the racemic antidepressant citalopram. This study evaluated the efficacy and tolerability of ESC in the treatment of major depressive disorder. 491 adult outpatients with an ongoing major depressive episode were randomly assigned to placebo; ESC, 10 mg/day; ESC, 20 mg/day; or citalopram, 40 mg/day; and entered an 8-wk double-blind treatment period following a 1-wk single-blind placebo lead-in. Clinical response was evaluated by the Montgomery-Asberg Depression Rating Scale, the 24-item Hamilton Rating Scale for Depression, the Clinical Global Impressions scales, the Hamilton Rating Scale for Anxiety, and patient-rated quality-of-life scales. ESC, at both doses, produced significant improvement at study endpoint relative to placebo on all measures of depression; significant separation of ESC from placebo was observed within 1 wk of double-blind treatment. Citalopram treatment also significantly improved depressive symptomatology compared with placebo; however, ESC, 10 mg/day, was at least as effective as citalopram, 40 mg/day, at endpoint. Anxiety symptoms and quality of life were also significantly improved by ESC compared with placebo. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Adolescent; Adult; Aged; Ambulatory Care; Antidepressant Drugs; Citalopram; Depressive Disorder; Dose-Response Relationship, Drug; Double-Blind Method; Drug Administration Schedule; Drug Therapy; Female; Humans; Major Depression; Male; Middle Aged; Placebos; Psychiatric Status Rating Scales; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Treatment Outcome; major depressive disorder; single isomer selective serotonin reuptake inhibitor escitalopram